MOBILIZATION OF DEVELOPMENT CAPITAL IN EAST NUSA TENGGARA: LEADERSHIP OF GOVERNOR VIKTOR BUNGTILU LAISKODAT - Pius Rengka; Daniel Daud Kameo; Intiyas Utami; Wilson M.A. Therik (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2025)
This study examines the social, political, and economic changes in East Nusa Tenggara Province during the leadership of Governor Viktor Bungtilu Laiskodat (2018–2023). As a marginal region, East Nusa Tenggara presents complex development challenges that demand an adaptive leadership model. Utilizing Pierre Bourdieu's theory of capital—social, economic, and cultural—this research analyzes how Governor Viktor Bungtilu Laiskodat’s strategies interacted with the local community’s habitus. A qualitative method was employed to explore the dynamics of the changes that occurred. The main findings include: (1) the strengthening of social capital through empowerment programs such as